Regulated control of virus replication by 4-hydroxytamoxifen-induced splicing - Zhao, Zhenghao; Wang, Busen; Wu, Shipo; Zhang, Zhe; Chen, Yi; Zhang, Jinlong; Wang, Yudong; Zhu, Danni; Li, Yao; Xu, Jinghan; Hou, Lihua; Chen, Wei (Frontiers in Microbiology, 2023)
Designing a modified virus that can be controlled to replicate will facilitate the study of pathogenic mechanisms of virus and virus-host interactions. Here we report a universal switch element that enables precise control of virus replication after exposure to a small molecule. Inteins mediate a traceless protein splicing-ligation process and we generated a series of modified Vesicular Stomatitis virus (VSV) with intein insertion into nucleocapsid, phosphoprotein or large RNA-dependent RNA polymerase of VSV. Two recombinant VSV, LC599 and LY1744, were screened for intein insertion in the large RNA-dependent RNA polymerase of VSV, and their replication was regulated in a dose-dependent manner with the small molecule 4-hydroxytamoxifen, which induces intein splicing to restore the VSV replication. Furthermore, in the presence of 4-hydroxytamoxifen, the intein-modified VSV LC599 replicated efficiently in animal model like prototype VSV. Thus, we present a simple, highly adaptable tool for regulating virus replication.